Enhancing Water and Oil Repellency of Teflon Surface By Imparting Micro-Rough Structures Using Simple One-Step - Khedir, Khedir R. (Science Journal of University of Zakho, 2017)
In this work, an easy one-step and inexpensive technique of mechanical wet sanding was used to impart micro structures into the Teflon surface that promotes super repellent properties toward water and the two moderate low surface tension organic liquids. Sandpapers with a wide range of grit sizes 60-1000, with associated particle sizes of 256-10 µm, were used to obtain physical modification of the Teflon surface. The roughened Teflon surface with the sandpaper of 400 grit size showed super repellency toward water, glycerol, and ethylene glycol with CAs as high as 158°, 150°, and 142°, respectively, as well as the low sliding angle of less than 2°, 5°, and 15°, respectively. The obtained results and the effect of roughness were explained in terms of both fundamental wetting models of Wenzel and Cassie-Baxter. The effect of a decrease in liquid surface tension on the length scale of imparted geometries and consequent wetting state was also concluded. Finally, the work of adhesion for the tested liquids while on the roughened Teflon surfaces were also determined using both Young-Dupre relation and the liquid’s SAs.